MACROECONOMIC DETERMINANTS OF LITHUANIAN GOVERNMENT SECURITY PRICES - Jurkšas, Linas; Kropienė, Rūta (Ekonomika, 2015)
This paper deals with the impact of macroeconomic fundamentals on Lithuanian government securities’ prices using quarterly data for the period 2000–2013, applying five major macroeconomic variables: gross domestic product, consumer prices, interest rates, money supply, and foreign direct investment. The two main goals of the paper are: 1) to identify macroeconomic variables which are the main driving forces behind debt security prices and 2) due to the lack of sufficient data on the Lithuanian government security index, to create and calculate a similar index from the primary and secondary market sovereign security prices. The research has been conducted using the methods of descriptive statistics, the vector autoregression model, the impulse response function, and the forecast error variance decomposition. The paper finds that, when consumer prices or interest rate rise up, sovereign security prices decline significantly and, on the other hand, money supply is the only factor that significantly and directly influences the government security prices. However, the effects of the gross domestic product and foreign direct investment were found to be statistically insignificant. Finally, the government security index is inert and rarely changes its long-term trend. These conclusions provide related persons with rich information in establishing the investment strategy or fiscal / monetary policy.
Keywords: macroeconomic determinants; government security index; government security prices; vector autoregression; impulse response function